The role of islamic family law programs in developing sharia-based solutions for cryptoasset inheritance disputes - Cenci Riestan; Artiyanto; Septia Novarisa (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The rapid expansion of digital financial technology has introduced cryptoassets as a new form of wealth, raising complex legal challenges in inheritance systems, particularly within Islamic law. The decentralized and encrypted nature of cryptoassets complicates asset identification, access, and valuation, potentially leading to disputes among heirs. This study aims to examine the role of Islamic Family Law programs in developing Sharia-based solutions for cryptoasset inheritance disputes. Employing a qualitative legal research design, the study integrates normative and socio-legal approaches by analyzing classical Islamic jurisprudence, contemporary legal scholarship, and regulatory frameworks related to digital assets. The findings indicate that cryptoassets can be classified as inheritable property (māl) under Islamic law, provided they possess economic value and can be legally transferred. However, their technological characteristics require adaptive legal interpretation to ensure fair and transparent distribution. Islamic Family Law programs play a strategic role through academic research, legal education, community engagement, and institutional collaboration in bridging classical inheritance principles with contemporary digital realities. This study contributes theoretically by extending the discourse on Islamic inheritance law into the domain of digital assets and practically by highlighting the importance of institutional involvement in addressing emerging legal challenges. The study concludes that strengthening Islamic legal education institutions is essential to ensure the relevance and adaptability of Sharia-based inheritance frameworks in the digital era.